Premenstrual dysphoric disorder as a potential predisposing factor for Alzheimer’s disease: a review - Yang, Jie; Cheng, Ming; Jiang, Zhaoshu; Du, Chunyu; Zhao, JinNan; Luo, Zhenliang; Zhang, Zhen (Frontiers in Endocrinology, 2025)
Premenstrual dysphoric disorder (PMDD) and Alzheimer’s disease (AD) differ significantly in terms of onset period and clinical manifestations. However, recent studies suggest that the two conditions may share potential links at the neuroendocrine and molecular levels. This review synthesizes current research progress and explores the intersecting biological pathways between PMDD and AD, with a particular focus on dynamic fluctuations in estradiol (E2) and allopregnanolone (ALLO), dysregulation of the γ-aminobutyric acid (GABA)ergic system and serotonergic (5-HT) neurotransmitter systems, and sex-specific vulnerability associated with the apolipoprotein E epsilon 4 (APOE ϵ4) allele. These mechanisms suggest that PMDD may serve as a potential biological precursor state for AD, offering valuable implications for early screening and intervention. The analysis provides new theoretical insights and research directions for identifying high-risk female populations, understanding sex differences in AD pathogenesis, and developing targeted therapeutic strategies.